2005
DOI: 10.1152/ajpgi.00307.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-dependent regulation of hepatic organic anion transporter gene transactivators in mouse liver

Abstract: Proinflammatory cytokines such as TNF-alpha and IL-1beta lead to downregulation of hepatic organic anion transporters in cholestasis. This adapted response is transcriptionally mediated by nuclear hormone receptors and liver-specific transcription factors. Because little is known in vivo about cytokine-dependent regulatory events, mice were treated with either TNF-alpha or IL-1beta for up to 16 h. Transporter mRNA expression was determined by Northern blot analysis, nuclear activity, and protein-expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
91
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 52 publications
(91 reference statements)
5
91
1
Order By: Relevance
“…Here, we found that multiple cytokines were activated by inflammatory perturbations, including significant and prolonged activation of TNF-a. In agreement with our findings, inflammatory cytokines downregulated the expression of bile canalicular transporters in the short term, including Abcc2, Abcb11, and other genes (16)(17)(18), although not Slco1b1 (19). Here, we found that downregulation of canalicular transporters can continue in the long term during ongoing activation of inflammatory cells and local release of relevant cytokines.…”
Section: Discussionsupporting
confidence: 92%
“…Here, we found that multiple cytokines were activated by inflammatory perturbations, including significant and prolonged activation of TNF-a. In agreement with our findings, inflammatory cytokines downregulated the expression of bile canalicular transporters in the short term, including Abcc2, Abcb11, and other genes (16)(17)(18), although not Slco1b1 (19). Here, we found that downregulation of canalicular transporters can continue in the long term during ongoing activation of inflammatory cells and local release of relevant cytokines.…”
Section: Discussionsupporting
confidence: 92%
“…These include Ntcp, Bsep, Oatp1, Oatp11, Mrp1, and Mrp9. The ability of LPS to down-regulate Ntcp, Oatp1, and Bsep mRNA expression has been demonstrated previously in vivo in rats and mice (Trauner et al, 1998;Hartmann et al, 2002;Geier et al, 2003;Cherrington et al, 2004;Siewert et al, 2004;Geier et al, 2005). The current results in IL-6(Ϫ/Ϫ) mice also confirm a previous report in which LPS administration resulted in transcriptional down-regulation of Ntcp, Bsep, and Oatp1 that was equally robust in WT and IL-6(Ϫ/Ϫ) mice (Siewert et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…Ntcp, Bsep, Oatp1, Oatp2, and Mrp2 mRNA expression in mice (Hartmann et al, 2002;Siewert et al, 2004;Geier et al, 2005). Given that both TNF-␣ and IL-1␤ have the ability to signal activation of NF-B-mediated transcription, each is likely to constitute at least one facet of compensatory signaling in the acute-phase response to LPS in TNFR1(Ϫ/Ϫ) and IL-1RI(Ϫ/Ϫ) mice.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…Sundaram et al (1998) have shown in a rabbit model that in the chronically inflamed ileum, Na + -BA cotransport is inhibited by decreases in both cotransporter affinity for BA and cotransporter numbers; specific but undetected immune-inflammatory mediators were invoked. A large body of evidence exists for cytokine-dependent deregulation of hepatobiliary BA transporters during inflammation (Geier et al, 2005). Therefore, we paid attention to biopsy in activedisease-inflamed regions.…”
Section: Discussionmentioning
confidence: 99%